2006
DOI: 10.1080/09593332708618717
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Direct Biofiltration of Surface Water for Reduction of Biodegradable Organic Matter and Biofilm Formation Potential

Abstract: Direct biofiltration of surface water may be considered as pre-treatment for membrane filtration, in order to reduce fouling. The biofiltration process was investigated with regard to biodegradable organic matter and biofilm formation, covering the annual variations under moderately cold climate conditions. Granular activated carbon (GAC) and two types of crushed expanded clay (EC) were compared as filter media. To assess the biological properties of the biofilters, viable biomass and respiratory activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
3
31
0
2
Order By: Relevance
“…These findings agree with the bacterial reductions found by Persson et al (2006), although we measured biological activity instead of the number of bacterial populations, and they are also in line with Meesters (2003), who found 30-to 40-fold lower ATP concentrations in biofiltered water than in feed water. Figure 3b shows the turbidity measured at the inlet and outlet streams of columns C-1 and C-2 in biofiltration processes Exp-1, Exp-2 and Exp-3 (see Table 5).…”
Section: Atp and Turbidity Evolution During Normal Biofiltrationsupporting
confidence: 80%
See 3 more Smart Citations
“…These findings agree with the bacterial reductions found by Persson et al (2006), although we measured biological activity instead of the number of bacterial populations, and they are also in line with Meesters (2003), who found 30-to 40-fold lower ATP concentrations in biofiltered water than in feed water. Figure 3b shows the turbidity measured at the inlet and outlet streams of columns C-1 and C-2 in biofiltration processes Exp-1, Exp-2 and Exp-3 (see Table 5).…”
Section: Atp and Turbidity Evolution During Normal Biofiltrationsupporting
confidence: 80%
“…ozonation) to reduce ozonation by-products (Servais et al, 1994;Carlson and Amy, 1997;. Another purpose of biofiltration is consumption of the biodegradable fraction of natural organic matter (NOM) in order to prevent downstream operational problems such as regrowth in pipelines (Servais et al, 1994;Huck et al, 1994;Urfer et al, 1997;Persson et al, 2006;Emelko et al, 2006). Furthermore, good efficiency in turbidity removal can also be attributed to biofiltration since it can act as a conventional physical filter, which results in acceptable filtration performances (Wang et al, 1995;Urfer et al, 1997;Emelko et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azzeh et al (2015) and Sadreddini (2013) examined direct biofiltration of river water prior to UF membrane filtration and reported reductions in membrane resistance as compared to nonbiologically treated river water. In similar studies performed by Huang et al (2011), Persson et al (2006, and Velten et al (2011), biofiltration was found to effectively reduce turbidity, organic, and biological activity levels prior to UF membrane processes. UF operating parameters, including the membrane MTC, were not reported (Huang et al, 2011;Persson et al, 2006;and Velten et al, 2011).…”
Section: Introductionmentioning
confidence: 50%